TEZAURUSLARDA LEKSIK-SEMANTIK MOHIYATNING IFODASI («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
Thesaurus is a dictionary that covers all the words of a certain language and fully reflects their usage in the text. In addition, ideographic dictionaries, in which lexical units related to a certain field of science are arranged in thematic order, and semantic, type-genus, synonymous and other relationships between these units, are among thesaurus dictionaries.Theoretically, the thesaurus is one of the possible models of the semantic system of the lexicon.
Keywords: thesaurus, dictionaries, lexical-semantic field, paradigmatic, syntagmatic, hierarchical relations.